The Influence of Blue Economy on Economic Growth of Sumenep Regency (International Forum of Researchers and Lecturers, 2024)
The urgency of conducting this study is that Sumenep Regency, located in the Madura archipelago, has a long coastline and access to abundant marine resources, but the challenges faced are overfishing, marine pollution, and coral reef damage are serious threats. In addition, sea level rise and changes in weather patterns can have a significant impact on the economy of coastal communities. The purpose of the research in this study is to test and analyze the influence of the blue economy on economic growth in Sumenep Regency. The method used is multiple regression for the period 2010 to 2023. The estimation results show that the variables of the fisheries sector, marine tourism, and environmental conservation have a positive impact on the economic growth of Sumenep Regency. This research is not only useful for optimizing regional potential, but also ensuring that the development carried out does not damage the ecosystem and continues to provide benefits for future generations.